Comparative Study of Molecular Docking, Structural, Electronic, Vibrational Spectra and Fukui Function Studies of Thiadiazole Containing Schiff Base – A Complete Density Functional Study. (31st December 2021) - Pandey, Anoop Kumar; Baboo, Vikas; Mishra, Vijay Narayan; Singh, V. K.; Dwivedi, Apoorva
Abstract: A detailed first principle study on the three thiadiazole containing Schiff base ligands having phenol, chloro and bromo combinations has been carried out [Density functional theory-DFT/B3LYP/6-311 G (d, p)]. The calculated structural properties show close resemblance with the literature data. The vibrational spectra of phenol-substituted molecule is calculated and compared with those obtained with experimental FTIR (Fourier Transform infrared spectroscopy) while for chloro-and bromo-substituted, it is predicted theoretically with vibartional assignments. TDDFT (Time dependent Density Functional Theory) calculations and Natural bond (NBO) analysis of title molecules have been also done with same level of theory. From NBO analysis, the lone pair electron n1 (O21) plays significant role in stabilization of compound A as compared to lone pair electron of n2 (Cl26), n2 (Br26) in B and C respectively. Some biological parameter Log P and Log S (Electro-topological indices) are also calculated (molecular docking calculations) which suggests that the derivatives of the title molecule have good ability to deliver drugs in various diseases. The reactivity of molecules using various descriptors (local) such as Fukui functions, local softness and electrophilicity as well as global i.e., electronegativity, hardness, HOMO (Highest occupied molecular orbital) - LUMO (Lowest unoccupied molecular orbital) gap etc. of the same are calculated and discussed.